Digital Support to Multimodal Community-Based Prehabilitation: Looking for Optimization of Health Value Generation - Barberan-Garcia, Anael; Cano, Isaac; Bongers, Bart C.; Seyfried, Steffen; Ganslandt, Thomas; Herrle, Florian; Martinez-Palli, Graciela (Frontiers in Oncology, 2021)
Prehabilitation has shown its potential for most intra-cavity surgery patients on enhancing preoperative functional capacity and postoperative outcomes. However, its large-scale implementation is limited by several constrictions, such as: i) unsolved practicalities of the service workflow, ii) challenges associated to change management in collaborative care; iii) insufficient access to prehabilitation; iv) relevant percentage of program drop-outs; v) need for program personalization; and, vi) economical sustainability. Transferability of prehabilitation programs from the hospital setting to the community would potentially provide a new scenario with greater accessibility, as well as offer an opportunity to effectively address the aforementioned issues and, thus, optimize healthcare value generation. A core aspect to take into account for an optimal management of prehabilitation programs is to use proper technological tools enabling: i) customizable and interoperable integrated care pathways facilitating personalization of the service and effective engagement among stakeholders; ii) remote monitoring (i.e. physical activity, physiological signs and patient-reported outcomes and experience measures) to support patient adherence to the program and empowerment for self-management; and, iii) use of health risk assessment supporting decision making for personalized service selection. The current manuscript details a proposal to bring digital innovation to community-based prehabilitation programs. Moreover, this approach has the potential to be adopted by programs supporting long-term management of cancer patients, chronic patients and prevention of multimorbidity in subjects at risk.
CRIS-Team Scopus Importer:2021-11-16
Keywords: behavioral change; eHealth; exercise training and nutrition counseling; mHealth; physical activity; prehabilitation; psychological well-being; technology – ICT